Hoitoonpääsyn hierarkiat Terveyskansalaisuus ja terveyspalvelut Suomessa 1900-luvulla - Harjula, Minna (Tampere University Press, 2015)
By analysing access to health services, the book explores the formation of health citizenship in Finland in the twentieth century. The book results in constructing four different historical layers of health citizenship, each of which emphasize different dimensions of accessibility and involve different inclusive and exclusive tensions. By exploring the topical questions of equality in health, the historical analysis makes it possible to broaden our understanding of welfare state.